2019
DOI: 10.1038/s41598-019-43875-3
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome differences between wild and captive black rhinoceros – implications for rhino health

Abstract: A number of recent studies have shown the importance of the mammalian gut microbiome in host health. In the context of endangered species, a few studies have examined the relationship between the gut microbiome in wild versus captive populations due to digestive and other health issues. Unfortunately, the results seem to vary across taxa in terms of captive animals having higher, lower, or equivalent microbiome diversity relative to their wild counterparts. Here, we focus on the black rhinoceros as captive ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
103
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 44 publications
10
103
3
Order By: Relevance
“…There was no significant difference in the alpha diversity measures between wild, captive, and domestic populations. Numerous, previous studies have also observed no difference in the alpha diversity between wild and captive populations of rhinoceros, musk deer, bovid, giraffes, aardvarks, and anteaters (Li et al, 2017;McKenzie et al, 2017;Gibson et al, 2019). In contrast, beta diversity significantly varied between populations, suggesting that distinct group of microbes inhabits the gut of wild, captive, and domestic populations.…”
Section: Discussionmentioning
confidence: 74%
“…There was no significant difference in the alpha diversity measures between wild, captive, and domestic populations. Numerous, previous studies have also observed no difference in the alpha diversity between wild and captive populations of rhinoceros, musk deer, bovid, giraffes, aardvarks, and anteaters (Li et al, 2017;McKenzie et al, 2017;Gibson et al, 2019). In contrast, beta diversity significantly varied between populations, suggesting that distinct group of microbes inhabits the gut of wild, captive, and domestic populations.…”
Section: Discussionmentioning
confidence: 74%
“…However, such large-scale metagenome assembly-based approaches have not been as extensively applied to most non-human vertebrates. The low amount of metagenome reads classified in some recent studies of the rhinoceros, chicken, cod, and cow gut/rumen microbiome suggests that databases lack much of the genomic diversity in less-studied vertebrates [8][9][10][11] . Indeed, the limited number of studies incorporating metagenome assembly hint at the extensive amounts of as-of-yet novel microbial diversity across the >66,000 vertebrate species on our planet.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a previous study compared the gut microbial communities of wild and captive black rhinos, and found that there was no signi cant difference in alpha diversity levels between wild and captive black rhinos, but signi cant differences in beta diversity, this study also found that bacterial groups traditionally associated with the ruminant gut of domestic animals have a higher relative abundance in captive rhinos. Functional pro ling results showed greater abundance of glycolysis and amino acid synthesis pathways in captive rhino microbiomes, representing an animal receiving sub-optimal nutrition with a readily available source of glucose but possibly an imbalance of necessary macro and micronutrients [22]. The phenotypic differences between the feeding systems examined here were primarily affected by the GIT lumen microbial structure.…”
Section: Microbiota Composition and Function Of Grazing And Drylot Goatsmentioning
confidence: 79%